2018
DOI: 10.5152/tpd.2018.5544
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Anti-Toxoplasma gondii Antibody Among First Trimester Pregnant Women Admitted to Nenehatun Maternity Hospital between 2013-2017 in Erzurum

Abstract: Our data was similar to the rest of the country. We suppose that every pregnant women should be educated about the disease and the transmission routes to raise an awareness and while the ones in the risk group should be screened instead of the whole group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
(18 reference statements)
1
8
1
1
Order By: Relevance
“…In the Americas context, the seroprevalence found in this study is lower than the 39.8% to 51% seroprevalence of T. gondii infection reported in pregnant women in Cali City, Colombia; 14 Bahia State, Brazil; 15 and 10 English-speaking Caribbean countries. 16 In addition, the seroprevalence found in pregnant women in Matehuala City is lower than the 11.1% to 21.9% seroprevalences of T. gondii infection reported in European countries including Spain, 17 Portugal, 18 Turkey 19 and Sweden. 20 It is not clear why the seroprevalence found in the current study is lower than those reported in pregnant women in other countries.…”
Section: Discussionmentioning
confidence: 74%
“…In the Americas context, the seroprevalence found in this study is lower than the 39.8% to 51% seroprevalence of T. gondii infection reported in pregnant women in Cali City, Colombia; 14 Bahia State, Brazil; 15 and 10 English-speaking Caribbean countries. 16 In addition, the seroprevalence found in pregnant women in Matehuala City is lower than the 11.1% to 21.9% seroprevalences of T. gondii infection reported in European countries including Spain, 17 Portugal, 18 Turkey 19 and Sweden. 20 It is not clear why the seroprevalence found in the current study is lower than those reported in pregnant women in other countries.…”
Section: Discussionmentioning
confidence: 74%
“…The most common symptoms seen in the human are lymphadenopathy and a flu-like clinical condition accompanied by fever, headache, sore throat, and muscle-and joint pain. However, it can cause severe symptoms in immunocompromised individuals and pregnant women [6,7].…”
Section: Cause and Transmissionmentioning
confidence: 99%
“…However, serious regional differences are also mentioned within the same country. In Turkey, T. gondii prevalence is high due to the climatic and local characteristics, and seropositivity among pregnant women varies between 22-47% [6]. The highest seropositivity was reported in Kahramanmaraş (47.1%) in pregnant women and in Şanlıurfa (69.5%) in a mixed population [13,14].…”
Section: Prevalencementioning
confidence: 99%
See 2 more Smart Citations